Історична географія та картографія України у військово-статистичних матеріалах ХІХ ст. - Нікічук, В. (Чорноморська минувшина, 2019)
У статті розглянуто розвиток історичної географії та картографії України на прикладі військово-статистичних матеріалів українських губерній Російської імперії. Проаналізовано вклад офіцерів Генерального Штабу Російської імперії у становлення історико-географічних досліджень. Охарактеризовано «Військово-статистичний огляд губерній та областей Російської імперії» та «Матеріалів для географії та статистики Росії, зібрані офіцерами Генерального штабу» як основне джерело військово-статистичних матеріалів ХІХ ст., які побіжно висвітлюють питання історичної географії. Також з’ясовано роль картографічної складової у дослідженнях військових офіцерів, зосередивши увагу на розробці топографічних карт під керівництвом Ф. Шуберта. The article considers the development of historical geography of Ukraine and cartography on the example of military statistical materials of the Ukrainian provinces of the Russian Empire. The contribution of officers of the General Staff of the Russian Empire to the formation of historical and geographical research is analyzed. The article describes "Military statistical survey of provinces and regions of the Russian Empire" and "Materials for geography and statistics of Russia collected by officers of the General staff" as the main source of military statistical materials of the XIX century, which casually cover the issues of historical geography. The research topics concerned the issues of defining the boundaries of provinces, toponymy of the region, geography of the population and ethnic component of the region, and so on. The role of the cartographic component in the study of military officers is also clarified. Attention is focused on the development of topographic maps as a separate component of military research. A significant role in the development of these maps played the Head of the corps of topographers F. Schubert. It was under his leadership that a special 10-verst map of Western Russia was developed. В статье рассмотрено развитие исторической географии Украины и картографии на примере военно-статистических материалов украинских губерний Российской империи. Проанализирован вклад офицеров Генерального штаба Российской империи в становление историко-географических исследований. Охарактеризовано «Военно-статистическое обозрение губерний и областей Российской империи» и «Материалы для географии и статистики России, собранные офицерами Генерального штаба» как основной источник военно-статистических материалов XIX в., которые освещают вопросы исторической географии. Также определена роль картографической составляющей в исследование офицеров, сосредоточив внимание на разработке топографических карт под руководством Ф. Шуберта.